2022
DOI: 10.1038/s41598-022-09085-0
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the periodontal pathogen Prevotella intermedia secretomes in biofilm and planktonic lifestyles

Abstract: Prevotella intermedia is an important species associated with periodontitis. Despite the remarkable clinical significance, little is known about the molecular basis for its virulence. The aim of this study was to characterize the secretome of P. intermedia in biofilm and planktonic life mode. The biofilm secretome showed 109 proteins while the planktonic secretome showed 136 proteins. The biofilm and the planktonic secretomes contained 17 and 33 signal-peptide bearing proteins, 13 and 18 lipoproteins, respecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The virulence factors mediating the contribution of P. intermedia to malignant transformation may be secreted proteins given that the proteinase K treatment of the conditioned medium eliminated these biological activities. In a recent report, an analysis of the functional protein association network of P. intermedia secretomes revealed that carbohydrate metabolism constitutes one of the three major groups in the network [45]. Among the components of the sugar metabolism network, glucose-6-phosphate isomerase (GPI), also known as autocrine motility factor (AMF), was identified.…”
Section: Discussionmentioning
confidence: 99%
“…The virulence factors mediating the contribution of P. intermedia to malignant transformation may be secreted proteins given that the proteinase K treatment of the conditioned medium eliminated these biological activities. In a recent report, an analysis of the functional protein association network of P. intermedia secretomes revealed that carbohydrate metabolism constitutes one of the three major groups in the network [45]. Among the components of the sugar metabolism network, glucose-6-phosphate isomerase (GPI), also known as autocrine motility factor (AMF), was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Other up-regulated surface proteins with a potential pathogenic role, identified in the periodontitis state, were the BspA of T. forsynthia ( Sharma et al, 1998 ; Mahalakshmi et al, 2018 ), the s-layer homology protein of Fretibacterium , and a lipoprotein cluster of Tannerella. Prevotella is known to secrete proteins in both planktonic and biofilm lifestyles ( Karched et al, 2022 ) and the increased transcription of the type VI secretion system protein Hcp suggests an important role of the Prevotella secretome in periodontitis. Elongation factor thermal unstable (EF-Tu) is one of the most abundant proteins in bacteria, with an important role in protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous proteomic analysis of P. intermedia compared the subcellular localization of proteins in planktonic and biofilm states (Karched et al, 2022 ). However, OMVs in P. intermedia have yet to be explored.…”
Section: Discussionmentioning
confidence: 99%